Historical Overview of the Evolution of Multidrug-Resistant Gram-Negative Infections in Tunisia from 1999 to 2019 - Lamia Kanzari; Sana Ferjani; Basma Mnif; Faouzia Mahjoubi; Mariem Zribi; Khaoula Meftah; Asma Ferjani; Emna Mhiri; Yomna Ben Lamine; Yosr Kadri; Habiba Naija; Manel Hamdoun; et al. (Antibiotics, 2025)
Background/Objectives: As antimicrobial resistance patterns of Gram-negative bacteria change over time, this study aimed to analyze the antimicrobial susceptibility trends of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii isolates in Tunisia. Methods: From 1999 to 2019, non-duplicate isolates of Gram-negative bacteria were collected from 11 Tunisian hospitals as part of an antimicrobial resistance surveillance program. Antimicrobial susceptibility testing was performed using the disk diffusion method according to the European Committee on Antimicrobial Susceptibility Testing guidelines. Results: Out of 213,434 isolates collected during the study period, 58.8% were E. coli, 22% were K. pneumoniae, 14.4% were A. baumannii, and 4.8% were P. aeruginosa, with 67% of the isolates sourced from urine samples. E. coli showed a significant increase in resistance to third-generation cephalosporins (3GC), from 5.4% in 2004 to 16.5% in 2019, but K. pneumoniae displayed a rising trend of resistance to imipenem, from 1% in 2005 to 18.6% in 2019; meanwhile, amikacin remained effective against K. pneumoniae isolates. P. aeruginosa did not exhibit a significant change in resistance to imipenem. A. baumannii had a high resistance rate to imipenem that increased from 34.5% in 2008 to 84.2% in 2019 and had low susceptibility rates to all other antibiotics tested. Conclusions: This study reveals high carbapenem resistance among K. pneumoniae and A. baumannii in Tunisia. A. baumannii shows alarming multidrug resistance that requires urgent control measures.